2023
DOI: 10.1186/s12866-023-02814-z
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient availability of roughages in isocaloric and isonitrogenous diets alters the bacterial networks in the whole gastrointestinal tract of Hu sheep

Abstract: Background The nutrient availability of roughages could affect the dietary utilization efficiency of ruminants even in isocaloric and isonitrogenous diets. Here, we analyzed the bacterial composition and their metabolic pathways in the gastrointestinal tracts (GITs) of Hu sheep fed with wheat straw (WS) instead of alfalfa (AL) in isocaloric and isonitrogenous diets, trying to explore the reasons from the perspective of GITs bacterial network structure changes. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…In our study, pathways related to amino acid, lipid, nucleotide, carbohydrate, inorganic ion, and coenzyme transport and metabolism, as well as translation and ribosomal structure biogenesis, exhibited an initial decline followed by an increase between 4 and 72 h. This trend suggests microbial competition for nutrients during the early fermentation stage [42], followed by enhanced growth due to nutrient release from cellulose degradation in later fermentation phases [43]. KEGG pathways analysis revealed that carbohydrate metabolism [44], amino acid metabolism [45], and energy metabolism pathways [45] had elevated relative abundances, underscoring their signi cance in the degradation of various roughage types [46]. Notably, ABC transporters were the most abundant functional pathway at level-3, indicating the diverse substrate-binding capabilities of the rumen microbiota [47,48].…”
Section: Discussionmentioning
confidence: 57%
“…In our study, pathways related to amino acid, lipid, nucleotide, carbohydrate, inorganic ion, and coenzyme transport and metabolism, as well as translation and ribosomal structure biogenesis, exhibited an initial decline followed by an increase between 4 and 72 h. This trend suggests microbial competition for nutrients during the early fermentation stage [42], followed by enhanced growth due to nutrient release from cellulose degradation in later fermentation phases [43]. KEGG pathways analysis revealed that carbohydrate metabolism [44], amino acid metabolism [45], and energy metabolism pathways [45] had elevated relative abundances, underscoring their signi cance in the degradation of various roughage types [46]. Notably, ABC transporters were the most abundant functional pathway at level-3, indicating the diverse substrate-binding capabilities of the rumen microbiota [47,48].…”
Section: Discussionmentioning
confidence: 57%
“…This trend suggests microbial competition for nutrients during the early fermentation stage [68], succeeded by enhanced growth due to nutrient release from cellulose degradation in later fermentation phases [69]. The KEGG pathways analysis revealed that carbohydrate metabolism [70], amino acid metabolism [71], and energy metabolism pathways [71] had elevated relative abundances, underscoring their significance in the degradation of various roughage types [72]. Notably, ABC transporters were the most abundant functional pathway at level-3, indicating the diverse substrate-binding capabilities of the rumen microbiota [73,74].…”
Section: Discussionmentioning
confidence: 96%
“…Not surprisingly, the results of our study found that dietary phytosterols did not affect the fermentation characteristics and alpha diversity of faecal bacteria in perinatal cows. Interestingly, we found that the phytosterols altered the relative abundances of faecal bacteria and their metabolites, partly because the alteration of forestomach digestion would change the digesta composition flowed to the hindgut and subsequently the bacterial network in ruminant faeces [41]. Firmicutes and Bacteroidota were the major bacterial phylum in the faeces of cows.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 89%